2022
DOI: 10.26418/jeep.v3i1.50496
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Students’ Difficulties in Writing Recount Text

Abstract: The purpose of this research was to explain difficulties faced by the eighth graders of SMP Bait Qur'an in writing a recount text. Descriptive qualitative was used to investigate this research. To obtain the data, a written test and a questionnaire were applied. To analyze the obtained data, data reducing, data displayed, content analysis, and drawing a conclusion were applied. Then the data were analyzed using percentage analysis. The test results showed that most students had poor ability in writing a recoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Students mostly need help in transferring their thoughts to their writings due to the effect of L1. Other studies, like Mastura et al (2022), Tursini & Prasetya (2020), Qasem et al (2022), also identified the impact of intralingual errors. They discovered in their studies that the fourth-semester students of the Department of English Education at Kanjuruhan University in Malang, MTsN 2 Aceh Besar students, and Yemeni secondary school students were making the most intralingual errors in their written compositions.…”
Section: Discussionmentioning
confidence: 79%
“…Students mostly need help in transferring their thoughts to their writings due to the effect of L1. Other studies, like Mastura et al (2022), Tursini & Prasetya (2020), Qasem et al (2022), also identified the impact of intralingual errors. They discovered in their studies that the fourth-semester students of the Department of English Education at Kanjuruhan University in Malang, MTsN 2 Aceh Besar students, and Yemeni secondary school students were making the most intralingual errors in their written compositions.…”
Section: Discussionmentioning
confidence: 79%
“…The reason for using cluster random sampling is that the 3 classes are both in the same grade, have the same material, have the same curriculum, and have the same background. According to Gay (1987: 110), a cluster random sampling strategy is one in which each group's sample is chosen at random, and they share a similar set of characteristics (Sukma, 2015).…”
Section: Data Sourcementioning
confidence: 99%
“…In showing composing, instructors additionally need to situate on a few sorts of composing information in particular information on the substance, information on composing steps to associate the thoughts, information on composing rules, and procedural information expected to utilize the three different sorts of information recorded as a hard copy a composed item Siahaan (2013). Those are as head segments to instructing keeping in touch with understudies.…”
Section: Theories Of Teaching Writingmentioning
confidence: 99%